PERANAN MULTIMEDIADALAMMENINGKATKAN PEMAHAMAN MAHASISWAPADA MATA KULIAH BIOLOGI SEL - Sumad, Sumad; Christijanti, Wulan; Marianti, Aditya (Universitas Negeri Semarang, 2011)
Cell Biology material that can not be seen with the naked eye and had to use the help tools (microscope) to be one reason for student difficulties in imagining is real. Time of lessons a limited cause not all the material can be given during lectures. Also by means of a simple (OHP) makes the material can not be described in detail. These facts affect the learning results obtained is not optimal, that is only 55% of students who obtained a value â¥ 70. Hence the need for a multimedia tool that is able to present the text, images, graphics, video, sound, and animation, so that students will gain knowledge as well as a concrete experience .The purpose of this study were: to determine the utilization of multimedia in Cell Biology course in improving student understanding. This research was conducted in 2 cycles with each cycle comprising three meetings. The first and second meetings for learning with multimedia and the third meeting was the discussion and evaluation. The main variables are the result of learning by supporting variables, such as student activity during the discussion, the performance of lecture and student responses . As an indicator of student performance is the result of learning gained â¥ 71 â¥ 80% of the whole class. The results showed in the first cycle the average results of student learning has reached 77.33 with the understanding level of 72.97%. The average study result on the second cycle is 81.77 with a level of understanding of 94.59%. To support variable (cycle I and II), â¥ 55% - 100% of students have been conducting activities during the discussion, score 77% - 100% for the performance of lecture and student responses is positive. Conclusion drawn is that the Cell Biology of learning with multimedia can increase students understanding. This is indicated by the average student learning outcomes is 77.33 with a level of understanding by 72, 97% in the first cycle increased on the second cycle was increased to 81.77 with a level of understanding reached 94.59%. Suggestions put forward is that it took a relatively long time in preparing a variety of research instruments and time efficiency in teaching and learning.